TRANSPARENCY AND LEGAL CERTAINTY IN WAITING TIME FEES: A CASE STUDY OF MAXIM IN PALU CITY - Nindia Saputri; Suhri Hanafi; Nadia Nadia (Tadayun: Jurnal Hukum Ekonomi Syariah, 2025)
This study investigates the legal implications of waiting time fees imposed in the Delivery Food and Shop service of the Maxim ride-hailing platform in Palu City. It is an empirical legal research that employs a statutory approach to analyze Law No. 8 of 1999 on Consumer Protection and a conceptual approach to examine the ijarah contract within the framework of Islamic commercial law (fiqh muamalah). Primary data were collected through field observations and interviews with Maxim users, driver-partners, and staff, while secondary data were obtained from legal documents and academic literature. The findings reveal that the current fee policy charging IDR 250 per minute after a 20-minute grace period lacks adequate transparency and user consent, thereby introducing elements of gharar (uncertainty) in sharia and potentially violating the principles of fair contracting in positive law. Although such fees are permissible under Islamic law when clearly agreed upon, the absence of upfront disclosure renders the contract problematic. The study recommends that Maxim improve price transparency and in-app information delivery to ensure fairness, legal certainty, and compliance with applicable legal norms. Abstrak Penelitian ini mengkaji implikasi hukum dari penerapan biaya waktu tunggu pada layanan Delivery Food and Shop oleh platform ojek online Maxim di Kota Palu. Penelitian ini merupakan penelitian hukum empiris yang menggunakan pendekatan perundang-undangan untuk menganalisis Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen serta pendekatan konseptual untuk mengkaji akad ijarah dalam kerangka hukum ekonomi Islam (fiqh muamalah). Data primer diperoleh melalui observasi lapangan dan wawancara dengan pengguna, mitra pengemudi, serta staf Maxim, sementara data sekunder diperoleh dari dokumen hukum dan literatur akademik. Hasil penelitian menunjukkan bahwa kebijakan tarif saat ini—Rp250 per menit setelah masa tunggu gratis 20 menit—tidak disertai dengan transparansi dan persetujuan awal dari pengguna secara memadai. Hal ini menimbulkan unsur gharar (ketidakpastian) dalam perspektif syariah dan berpotensi melanggar prinsip keadilan kontraktual dalam hukum positif. Meskipun biaya tersebut dibolehkan dalam hukum Islam jika disepakati secara jelas, ketiadaan informasi yang disampaikan sejak awal membuat kontrak menjadi bermasalah. Studi ini merekomendasikan agar Maxim meningkatkan transparansi tarif dan penyampaian informasi dalam aplikasi untuk menjamin keadilan, kepastian hukum, dan kepatuhan terhadap norma hukum yang berlaku.